2016
DOI: 10.1007/s11906-016-0658-1
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Induced Hypertension: Brain Signaling Pathways

Abstract: Obesity greatly increases the risk for cardiovascular, metabolic, and renal diseases and is one of the most significant and preventable causes of increased blood pressure (BP) in patients with essential hypertension. This review high-lights recent advances in our understanding of central nervous system (CNS) signaling pathways that contribute to the etiology and pathogenesis of obesity-induced hypertension. We discuss the role of excess adiposity and activation of the brain leptin-melanocortin system in causin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 88 publications
0
31
0
Order By: Relevance
“…An increase in serum osmolarity by salt has been shown to activate the aldose reductase-fructokinase pathway in the liver and hypothalamus that can over time lead to metabolic syndrome and elevations in blood pressure [3]. The increase in serum and SNS osmolarity stimulates vasopressin and leptin release [34], and the latter can activate the SNS sympathetic response to raise blood pressure [35]. An increase in SNS osmolarity also stimulates the production of cardiotonic steroids (Na-K ATPase) inhibitors that cause peripheral vasoconstriction [36].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in serum osmolarity by salt has been shown to activate the aldose reductase-fructokinase pathway in the liver and hypothalamus that can over time lead to metabolic syndrome and elevations in blood pressure [3]. The increase in serum and SNS osmolarity stimulates vasopressin and leptin release [34], and the latter can activate the SNS sympathetic response to raise blood pressure [35]. An increase in SNS osmolarity also stimulates the production of cardiotonic steroids (Na-K ATPase) inhibitors that cause peripheral vasoconstriction [36].…”
Section: Discussionmentioning
confidence: 99%
“…63 In contrast, RDN has been shown to be highly effective in reducing BP in obesity-induced HT which is associated with increased RSNA and may account for 65-75% of the risk for primary HT as well being a major contributor to treatment resistant HT. 8,21,42,[138][139][140][141] The drugs used to treat HT may also influence BP responses to RDN. Experimental studies indicate that the effects of increased RSNA on kidney function are mediated via direct αadrenergic stimulation of tubular NaCl reabsorption as well as β-adrenergic stimulation of renin release and subsequent ANG II formation which, in turn, has multiple effects to increase NaCl reabsorption.…”
Section: In Which Patients Is Rdn Most Likely To Effectively Reduce Bp?mentioning
confidence: 99%
“…A large number of preclinical investigations have identified the central pathways involved in regulating sympathetic outflow in obesity (for a comprehensive review, see Refs. [38][39][40]. While the central regulation of sympathetic outflow in obesity is undoubtedly complex, involving multiple pathways and neurotransmitter systems, a number of studies have demonstrated the importance of the hypothalamic leptin−melanocortin system in sympathetic regulation in models of obesity, with α-melanocortin−stimulating hormone being particularly effective in stimulating renal sympathetic nerve activity in high-fat fed rabbits.…”
Section: Central Regulation Of Sympathetic Activity In Obesitymentioning
confidence: 99%